(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
Traditional meaning of the word sovereignty is associated with indisputable authority of the country to legitimately conduct effective control on its territory managing economic, legal, political, cultural and all other aspects of social life in accordance with the internal will and its own interests. However, contemporary understanding of the sovereignty is more complex and it can be noted that modern sovereignty of nation is primarily related to the economic strength in the context of growth and development of economy. The aim of this paper is to review role and importance of the entrepreneurship as a central element of market economy function, which represents one of the crucial requirements on Bosnia-Herzegovinian path towards European Union, Euro-Atlantic and regional integrations. Entrepreneurship as a source of innovation in a society which improves productivity as well as competitiveness is presented in regard to Bosnian-Herzegovinian context focusing on unquestionable correlation with the economic growth and development. Particular attention is dedicated in explanation of entrepreneurial philosophy significance within companies regardless of their size, ownership structure or economic activities as an appropriate recipe of effective management in today´s highly dynamic business environment which is characterized by continuity of changes and rapid development of technology. The pace of future entrepreneurship development in Bosnia and Herzegovina is evaluated, meanwhile institutional and economic elements that potentially represent specific barriers and challenges are identified. Finally, recommendations of economic policy and further actions are highlighted with aim to intensify the development of entrepreneurship as an important pillar of economic growth in Bosnia and Herzegovina and thus strengthening the sovereignty and international influence of the country.